La « Montagne raciale » : et après ? Parcours identitaires dans deux romans ghanéens contemporains - Marie-Jeanne Gauffre (Anglophonia)
Afro-American poet Langston’s Hughes’s challenge to the "Negro artist" in 1926—to run away from "the race towards whiteness" and climb the "racial mountain" in order to "discover himself and his people" reverberated throughout the colonial and later postcolonial world. Echoes of his plea have long been found in West African literary works concerned with restoring a positive image of the black self, but other "mountains" to be conquered have more recently come into view, especially in women’s writings. Two Ghanaian novels, Our Sister Killjoy or Reflections from a Black-Eyed Squint (1977), by Ama Ata Aidoo, and Beyond the Horizon (1995), by Amma Darko, illustrate some transformations of the issue raised by Hughes